Population policies, demographic structural changes, and the Chinese household saving puzzle - Suqin Ge; Dennis Tao Yang; Junsen Zhang (Institute for the Study of Labor (IZA), 2012)
Using combined data from population censuses and Urban Household Surveys, we study the effects of demographic structural changes on the rise in household saving in China. Variations in fines across provinces on unauthorized births under the one-child policy and in cohort-specific fertility influenced by the implementation of population control policies are exploited to facilitate identification. We find evidence that older households with a reduced number of adult children save more because of old-age security concerns, middle-aged households experience an increase in saving due to the lighter burden of dependent children, and younger households save more because of having fewer siblings to share the responsibility of parental care. These findings lend support to a simple economic model in which the effects of population control policies are investigated in the context of household saving decisions in China.
Keywords: E21; J11; J13; 330; household saving; one-child policy; demographic structure; cohort analysis; China; Sparen; Privater Haushalt; Familienplanung; Bevölkerungspolitik; Bevölkerungsstruktur; Theorie; China